Mundo clásico y ciencia ficción o cómo construir una utopía feminista: The Gate to Women’s Country de Sheri Tepper - Rosario López Gregoris; Cristina Salcedo González (Eugesta, 2024)
This paper offers an analysis of Sheri Tepper’s novel, The Gate to Women’s Country, through the lenses of Classical Reception and feminist reinterpretation, aligning with Hardwick’s theoretical framework and drawing upon the specific conceptual propositions of Ostriker, Keen and Durand. Tepper’s narrative comprises both utopian and dystopian elements. In her utopian projection, a Greek tragedy is reimagined as Iphigenia in Ilium, wherein she introduces a dialogue with the deceased to underscore the inherent violence of men and its consequences for women and children. In the dystopian projection, she indirectly utilises the myth of Persephone and Demeter, with a notable emphasis on the catabatis motif, implicitly employed to depict the harrowing and violent experiences faced by the central character, Stavia. This portrayal of Hades, transposed to Tepper’s envisioned society, serves as a cautionary tale highlighting the perils that women encounter when they lack control, influence or a voice.